Optimizing School-Based Feeding Program Management: A Comparative Literature Review of Lessons from the Philippines for Indonesia - Hansiden, Polii Einjelheart; Kijai, Jimmy; Rantung, Margareth (Iapa Proceedings Conference, 2025)
Improving student nutrition is a critical challenge in developing nations. As Indonesia prepares to launch its ambitious Makan Bergizi Gratis (MBG) program, this study presents a strategic roadmap by comparatively analyzing the Philippines’ established School-Based Feeding Program (SBFP). Institutionalized by law, the SBFP successfully rehabilitated 62% of severely wasted children and improved school attendance. However, the program offers crucial cautionary lessons. Severe Monitoring and Evaluation (M&E) data inconsistencies were found, with only 43% of beneficiaries being correctly verified. More critically, nutritional gains proved unsustainable, as only 48% of children maintained normal status 12 months post-program. Based on this analysis, strategic recommendations are formulated for Indonesia: establishing a permanent legal framework to ensure sustainability, adopting a hybrid logistics model (Central Kitchens in urban areas and Home-Grown School Feeding in rural regions), and mandating the integration of comprehensive nutrition education with a robust digital M&E system. These steps are essential to ensure accountability and transform a short-term intervention into a permanent human capital investment.